PREVENTING SELFISHNESS DATA ACCESS IN WIRELESS NETWORK - Kumar, Dr. M.Vinoth; Arasu, G.Tholkappia (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
A mobile adhoc network (MANET) is a wireless network among mobile device. A mobile adhoc network (MANET) is a constantly self-configuring, infrastructure-less network of mobile devices connected wirelessly. Each device in a MANET is free to move independently in any direction, and will therefore modify its relations to further devices regularly .Selfish assign nodes from direct based on simulation result analysis on MANET. Mobile ad-hoc networks (MANETs) rely on collaboration of all contribute nodes. Thus they are vulnerable to self-interested nodes using the net without providing own resources, as well as hateful nodes attacking the network communications.